Palivizumab Prophylaxis for Respiratory Syncytial Virus: Examining the Evidence Around Value. (7th February 2018) - Olchanski, Natalia; Hansen, Ryan N; Pope, Elle; D'Cruz, Brittany; Fergie, Jaime; Goldstein, Mitchell; Krilov, Leonard R; McLaurin, Kimmie K; Nabrit-Stephens, Barbara; Oster, Gerald; Schaecher, Kenneth; Shaya, Fadia T; et al.
Abstract: Respiratory syncytial virus (RSV) infection is the most common cause of lower respiratory tract infection and the leading cause of hospitalization among young children, incurring high annual costs among US children under the age of 5 years. Palivizumab has been found to be effective in reducing hospitalization and preventing serious lower respiratory tract infections in high-risk infants. This paper presents a systematic review of the cost-effectiveness studies of palivizumab and describes the main highlights of a round table discussion with clinical, payer, economic, research method, and other experts. The objectives of the discussion were to (1) review the current state of clinical, epidemiology, and economic data related to severe RSV disease; (2) review new cost-effectiveness estimates of RSV immunoprophylaxis in US preterm infants, including a review of the field's areas of agreement and disagreement; and (3) identify needs for further research.